Environmental drivers of litter- and soil-dwelling springtail communities across European forests, assessed by morphotaxonomy and soil DNA metabarcoding - Ivano Brunner; Beat Frey; Maria J.I. Briones; Jérome Cortet; Xavier Domene; Juliane Filser; Aline Frossard; Davey L. Jones; Paul Henning Krogh; Juha Mikola; Olaf Schmidt; José Paulo Sousa; et al. (Applied Soil Ecology, 2026)

Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Comparing soil microarthropod communities derived directly from soil DNA metabarcoding with those from morphological assessment in a drought-prone and irrigated pine forest - Jessica Cuartero; Ivano Brunner; Marcus Schaub; Dariusz J. Gwiazdowicz; Piotr Skubała; Jiayi Qin; Paul Henning Krogh; Beat Frey (Applied Soil Ecology, 2025)

Comparison of RT-qPCR With Branched DNA to Quantify a Lipid Nanoparticle–Encapsulated mRNA Therapeutic in Serum and Liver Tissue Samples From Nonclinical PK Studies - Jessica Ortiz; Laura Brunner; Lei Ci; Rena Baek; Darshana Jani; Jean-Claude Marshall; Jason Pennucci (The AAPS Journal, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

More than a decade of irrigation alters soil nematode communities in a drought-prone Scots pine forest - Jessica Cuartero; Beat Frey; Reinhard Eder; Ivano Brunner (Applied Soil Ecology, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Associations between mycoestrogen exposure and sex steroid hormone concentrations in maternal serum and cord blood in the UPSIDE pregnancy cohort - Carolyn W. Kinkade; Lauren M. Aleksunes; Anita Brinker; Brian Buckley; Jessica Brunner; Christina Wang; Richard K. Miller; Thomas G. O'Connor; Zorimar Rivera-Núñez; Emily S. Barrett (International Journal of Hygiene and Environmental Health, 2024)

Protective role of the placental efflux transporter BCRP/ABCG2 in the relationship between prenatal cadmium exposure, placenta weight, and size at birth - Emily S. Barrett; Zorimar Rivera-Núñez; Kylie Getz; Pamela Ohman-Strickland; Ranran Zhang; Danielle Kozlosky; Cathleen L. Doherty; Brian T. Buckley; Jessica Brunner; Richard K. Miller; Thomas G. O'Connor; Lauren M. Aleksunes (Environmental Research, 2023)

Prenatal perfluoroalkyl substances exposure and maternal sex steroid hormones across pregnancy - Zorimar Rivera-Núñez; Carolyn W. Kinkade; Leena Khoury; Jessica Brunner; Hannah Murphy; Christina Wang; Kurunthachalam Kannan; Richard K. Miller; Thomas G. O'Connor; Emily S. Barrett (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)